Eye-hand coordination asymmetries in manual aiming - Lavrysen, A.; Elliott, D.; Buekers, M. J.; Feys, P.; Helsen, W. F. (Journal of Motor Behavior, 2007)
The authors investigated whether movementplanning and feedback-processing abilities associated with the 2 hand-hemisphere systems mediate illusion-induced biases in manual aiming and saccadic eye movements. Although participants' (N = 23) eye movements were biased in the direction expected on the basis of a typical Müller-Lyer configuration, hand movements were unaffected. Most interesting, both leftand right-handers' eye fixation onset and time to hand peak velocity were earlier when they aimed with the left hand than they were when they aimed with the right hand, regardless of the availability of vision for online movement control. They thus adapted their eye-hand coordination pattern to accommodate functional asymmetries. The authors suggest that individuals apply different movement strategies according to the abilities of the hand and the hemisphere system used to produce the same outcome.